Relaxation dynamics of carboxylated nitrile rubber filled with organomodified nanoclay (eXPRESS Polymer Letters)
In order to improve the physical properties of elastomers and to get more insight into the polymer dynamics close to filler interphases a carboxylated nitrile rubber (XNBR) was filled with up to 10 phr of layered silicate and investigated by dielectric and dynamic-mechanical analysis as well as by IR spectroscopy. Three relaxation processes have been detected beside the electrode polarization effect obtained in dielectric measurements. The relaxation process at low temperatures can be assigned to the β-process due to the rotational motion of side groups. Its temperature dependence follows an Arrhenius-like behaviour and there is no significant change in the shape of this process with the incorporation of filler. The glass transition at medium temperature shows a Vogel-Fulcher-dependence but seems to be independent of filler as well. At higher temperatures a new relaxation process was detected which is probably due to the formation of zinc-carboxyl-clusters. In dielectric and dynamic-mechanical measurements this process increases with increasing loading of organoclay and is shifted to higher temperature.